Analisa Stres dan Cara Mengatasi dengan Pendekatan menurut Hipnoterapi - Suminah; Ciputri, Leony (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Stress is the body's nonspecific response to demands that it cannot manage according to its capabilities. Every person encounters problems in life, and people react differently to these problems. As one ages, the sources of stress increase because the environment they face becomes broader than before. Understanding the root causes is essential to manage stress effectively. How stress arises and what triggers it can be explored from the subconscious mind, and all root problems can be analyzed to provide suggestions, so that the handling can be successful in achieving better living behaviors. This study aims to understand and analyze how stress arises and the approaches that can be taken according to hypnotherapy. The expected outcome of hypnotherapy is that stress can be controlled, allowing a person to live a better life, free from stress. With hypnotherapy, the power of the subconscious mind that influences thoughts can be directed towards a more positive direction.